2023
DOI: 10.48048/tis.2023.5425
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Based Detection and Staging of Breast Cancer from Blood Using Raman Spectroscopy and Deep Learning Technique

Abstract: Breast cancer (BC) or breast neoplasm is causing major menace to the life of women around the world. The significance of early detection and staging of BC has been substantial in diagnosing protocol. This work aims to develop an automated system that combines multivariate data analysis (PCA - principal components analysis) with ensemble recurrent neural network models (stacked OGRU-LSTM) to identify Raman spectral characteristics that can be used as spectral cancer markers for the detection of BC progression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Shu 24 et al integrated Raman spectroscopy with partial least squares-linear discriminant analysis (PLS-LDA) and successfully established a Raman staging model to distinguish different stages of nasopharyngeal carcinoma (NPC), involving nasopharyngeal carcinoma stages i, ii, iii, and iv of cancer. Selvarani et al 25 combined multivariate data analysis with an integrated recurrent neural network model (stacked OGRU-LSTM) to identify Raman spectroscopic markers for the progression and staging of breast cancer (BC). The research findings demonstrated that the stacked OGRU-LSTM model performs exceptionally well in breast cancer detection and effectively distinguishes various breast cancer stages using multivariate data analysis technology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shu 24 et al integrated Raman spectroscopy with partial least squares-linear discriminant analysis (PLS-LDA) and successfully established a Raman staging model to distinguish different stages of nasopharyngeal carcinoma (NPC), involving nasopharyngeal carcinoma stages i, ii, iii, and iv of cancer. Selvarani et al 25 combined multivariate data analysis with an integrated recurrent neural network model (stacked OGRU-LSTM) to identify Raman spectroscopic markers for the progression and staging of breast cancer (BC). The research findings demonstrated that the stacked OGRU-LSTM model performs exceptionally well in breast cancer detection and effectively distinguishes various breast cancer stages using multivariate data analysis technology.…”
Section: Introductionmentioning
confidence: 99%
“…The main goal of our multitask network model is to process multiple interrelated tasks simultaneously, utilizing shared information extracted from common features. 27 In this way, we enhance our overall understanding of the data distribution, which improves the performance of each individual task. 28 This simplified approach can perform three classification tasks within the scope of a single network model, potentially revealing key features embedded in Raman spectral data.…”
Section: Introductionmentioning
confidence: 99%